Fragmentation of thin lenses - Brodskii, R.Ye.; Kulik, T.V. (Functional Materials, 2016)
In the paper it was investigated the case of the quasi-two-dimensional fragmentation - fragmentation of the round lenses considering dependence of the probability of splitting on energy required for this, i.e. the surface of split area. lenses - plates with variable thickness. In the paper lenses of several types was investigatet, for each case fragment mass distribution was obtained analytically. In the general case - in parametric form and asymptotics explicitly.